Spatial Redistributions of Regional Economic Activity in Central Java (Direct Error Correction Model Causality Approach) - Jihad Lukis Panjawa; Bhimo Rizky Samudro (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
This study analyzes spatial inequality through a causal relationship between inequality and economic growth within-recidency, between-recidency and overall in Central Java.The analytical tool used is the Direct Error Correction Model causality. This study shows that spatial concentrations throughout the observation period are quite high. In the 2001-2008 period there was an increasing tendency for spatialconcentration, reflecting the decline in the distribution of the Gross Regional Domestic Product (GRDP) share of districts and cities in Central Java. We also obtained similar findings in a number of regions both within and between-recidency. Post-2008, spatial concentration tends to decrease, indicating the distribution of the Gross Regional Domestic Product share. Other findings indicate a one-way relationship shown economic growth towards inequality. Another important contribution is that economic growth in inequality only occurs in the long term. Thus there has been convergence because of the increase ineconomic growth which is able to reduce inequality in all areas of Central Java, including within and between-recidency. This proves that during the implementation of regional autonomy there is a spread effect greater than the backwash effect in Central Java, including within and between-recidency.